(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purposes of this study were to determine the factors influencing consumer behavior, the marketing mix factors, psychological factors, and social factor on buying products online. This was a quantitative research using questionnaire as a tool to collect 400 online customers and the data was analyzed for both descriptive and inferential statistics, namely percentage, mean, standard deviation, Chi Square, and multiple regression analysis were reported.The results of the study showed that most of respondents were female, aged 21-30 years old, single status, bachelor or equivalent degree holders, worked for private industries, and earned a monthly income of 20,001-30,000 baht. The overall picture of the opinions on marketing mix factors, psychological factors, and social factor on buying products online at a high level consisted of conveniently to purchase, spent 1,400 baht 1-2 times during evening through Facebook at a time, and paying bill by using Internet banking. The results of hypothesis testing revealed that the different person factors, such as gender, age, level of education, and average monthly income affected consumer decision on purchasing products online, but the different personal factors as marital status was not affected. The factors of marketing mix, such as products, prices, distribution channel, marketing promotion, psychological factors, such as motivation, attitudes, perception, learning, Beliefs and social factors, such as family, social class and culture influenced the buying behavior through online shops at statistically significant 0.05 level.Recommendations from the study results were that online marketing administrative officers should emphasize on variety of products, beautiful designed, fashionable, and choices of payment.